Differences in kinematics and energy cost between front crawl and backstroke below the anaerobic threshold - Gonjo, T.; McCabe, C.; Sousa, A.; Ribeiro, J.; Fernandes, R. J.; Vilas-Boas, J. P.; Sanders, R. (European Journal of Applied Physiology, 2018)
Purpose: The purpose of this study was to determine kinematic and energetic differences between front crawl and backstroke performed at the same aerobic speeds. Methods: Ten male competitive swimmers performed front crawl and backstroke at a pre-determined sub-anaerobic threshold speed to assess energy cost (through oxygen uptake measurement) and kinematics (using three-dimensional videography to determine stroke frequency and length, intra-cycle velocity fluctuation, three-dimensional wrist and ankle speeds, and vertical and lateral ankle range of motion). For detailed kinematic analysis, resultant displacement, the duration, and three-dimensional speed of the wrist during the entry, pull, push, and release phases were also investigated. Results: There were no differences in stroke frequency/length and intra-cycle velocity fluctuation between the swimming techniques, however, swimmers had lower energy cost in front crawl than in backstroke (0.77 ± 0.08 vs 0.91 ± 0.12 kJ m-1, p < 0.01). Slower three-dimensional wrist and ankle speeds under the water (1.29 ± 0.10 vs 1.55 ± 0.10 and 0.80 ± 0.16 vs 0.97 ± 0.13 m s-1, both p < 0.01) and smaller ankle vertical range of motion (0.36 ± 0.06 vs 0.47 ± 0.07 m, p < 0.01) in front crawl than in backstroke were also observed, which indirectly suggested higher propulsive efficiency in front crawl. Conclusion: Front crawl is less costly than backstroke, and limbs motion in front crawl is more effective than in backstroke.